2022
DOI: 10.1021/acs.langmuir.2c01564
|View full text |Cite
|
Sign up to set email alerts
|

Evaporative Deposition of Surfactant-Laden Nanofluid Droplets over a Silicon Surface

Abstract: Morphologies of evaporative deposition, which has been widely applied in potential fields, were induced by the competition between internal flows inside evaporating droplets. Controlling the pattern of deposition and suppressing the coffeering effect are essential issues of intense interest in the aspects of industrial technologies and scientific applications. Here, evaporative deposition of surfactant-laden nanofluid droplets over silicon was experimentally investigated. A ring-like deposition was formed afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…50 Increasing surfactant concentration over the surfactant critical micelle concentration (CMC) is favorable to achieve uniform crack-free deposits. 35 Here, the presence of Marangoni flows could be one reason for fewer crack deposits from the latte droplets compared to the coffee droplets. The invariant latte surface tension to the fraction of milk (from ϕ milk = 20−100%), indicating that all latte solutions are over the CMC concentration.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…50 Increasing surfactant concentration over the surfactant critical micelle concentration (CMC) is favorable to achieve uniform crack-free deposits. 35 Here, the presence of Marangoni flows could be one reason for fewer crack deposits from the latte droplets compared to the coffee droplets. The invariant latte surface tension to the fraction of milk (from ϕ milk = 20−100%), indicating that all latte solutions are over the CMC concentration.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…It is worthwhile to note that surfactant-induced flows may counteract capillary flows inside an evaporating water droplet and cause uniform deposit patterns (Marangoni effect) . Increasing surfactant concentration over the surfactant critical micelle concentration (CMC) is favorable to achieve uniform crack-free deposits . Here, the presence of Marangoni flows could be one reason for fewer crack deposits from the latte droplets compared to the coffee droplets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 While thermal Marangoni flow in pure water droplets at room temperature is not well understood yet, 31,32 the presence of surfactants can have a strong impact on the flow and contact line deposition. [33][34][35] However, the physics of the problem is very complicated in such a way that different types of surfactants can have different effects on the interfacial flow of evaporating sessile droplets. 36 It was shown that insoluble surfactants do not produce Marangoni vortices, 37 but soluble surfactants can drive considerable recirculation.…”
Section: Introductionmentioning
confidence: 99%
“…The interplay between capillary and Marangoni flows in evaporating droplets of complex fluids such as polymer solutions or colloidal suspensions leads to the formation of unique patterns. [33][34][35][36] These morphological patterns of drying bio-colloidal droplets can be utilized in biomedical applications and medical diagnosis. [37] Pathak et al [38] investigated the effect of salt concentration in the aqueous solution of bovine serum albumin on the patterns left by evaporating sessile droplets.…”
Section: Introductionmentioning
confidence: 99%